1996
DOI: 10.1017/s0033291700033808
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological syndromes in the functional psychoses: associations with course and outcome

Abstract: SynopsisThe aim of this study was to identify underlying dimensions of psychopathology in a cohort of patients with functional psychosis of recent onset, and to examine their prognostic value. Factor analysis of the psychopathological features of 166 consecutively admitted patients with functional psychosis of recent onset revealed seven psychopathological dimensions, which explained 63% of the variance. Five of these seven syndromes bore differential associations with subsequent treatment and illness course, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
116
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 55 publications
21
116
1
1
Order By: Relevance
“…[37][38][39][40][41] Family studies evidenced a moderate but significant heritability for all psychopathological factors. [42][43][44][45][46][47][48] The factors are stable over time 49 and they are correlated with regional anatomical abnormalities. 50 We have previously detected and replicated an association of the DRD2 S311C variant with disorganized symptomatology of schizophrenia.…”
mentioning
confidence: 99%
“…[37][38][39][40][41] Family studies evidenced a moderate but significant heritability for all psychopathological factors. [42][43][44][45][46][47][48] The factors are stable over time 49 and they are correlated with regional anatomical abnormalities. 50 We have previously detected and replicated an association of the DRD2 S311C variant with disorganized symptomatology of schizophrenia.…”
mentioning
confidence: 99%
“…The first includes bizarre behaviour, catatonia, inappropriate affect and difficult rapport (inappropriate-catatonia), the second delusions of passivity, bizarre delusions, thought interference and hallucinations (delusions-hallucinations), the third mania, grandiose delusions and relationship psychotic/affective symptoms (mania), the fourth insidious onset, blunting of affect and age of onset (insidious-blunting), the fifth depression and depressive delusions (depression) and the last two lack of insight and paranoid delusions respectively. In a study including 66 patients with schizophrenia, Cardno et al (1997) found even eight factors that are to some extent quite different from the seven described by Van Os et al (1996). In a mixed sample of psychotic and depressed patients, Serretti et al (1996) identified on the basis of 38 items three psychosis-factors (excitement, disorganization and delusion) and one affective factor (depression).…”
Section: Operational Criteria and Polydiagnostic Approachmentioning
confidence: 85%
“…By using 20 items, Van Os et al (1996) demonstrated seven underlying structures that accounted for 63% of the variance. The first includes bizarre behaviour, catatonia, inappropriate affect and difficult rapport (inappropriate-catatonia), the second delusions of passivity, bizarre delusions, thought interference and hallucinations (delusions-hallucinations), the third mania, grandiose delusions and relationship psychotic/affective symptoms (mania), the fourth insidious onset, blunting of affect and age of onset (insidious-blunting), the fifth depression and depressive delusions (depression) and the last two lack of insight and paranoid delusions respectively.…”
Section: Operational Criteria and Polydiagnostic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it reduces the individual lifespan by on average of 15-20 years [2]. Schizophrenia is characterized by a heterogeneous outcome, with a smaller proportion (20-50%) of patients experiencing recovery or significant improvement, compared to a majority of them with a course characterized by multiple episodes and increasing impairment [3].…”
Section: Introductionmentioning
confidence: 99%